ISLAMISASI ILMU PENGETAHUAN KONTEMPORER SEBAGAI KEBUTUHAN DALAM PENGEMBANGAN PENDIDIKAN ISLAM - Sudarto, Sudarto (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2020)
ABSTRACTIslamization of Science is a necessity for the world of Islamic education today. Western civilization with its worldview has hegemony in almost all lines of the academic world. As a result, standards, policies, and concepts of science are more determined by Western perspectives than Islamic perspectives. This issue becomes an increasingly important issue for immediate response because the effects of secularization transplanted into science in the Islamic world have led to the confusion of the concept of science. Thus the Islamization of contemporary science is a necessity that cannot be negotiable in the development of Islamic education.Â Keywords: Islamization of science, Western civilization, science